Conductive silver glue and its preparation method and application

By adding hydroxyethylated bisphenol fluorene epoxy resin and other epoxy resins to the conductive silver glue, the composition is optimized, and the problems of insufficient bonding strength and high resistivity of conductive silver glue in high temperature environments are solved, and the conductivity is improved Effect and service life.

CN115595089BActive Publication Date: 2024-12-17BEIJING KMT TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211231498.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-09
Publication Date
2024-12-17
Estimated Expiration
2042-10-09

AI Technical Summary

Technical Problem

The bonding strength of existing conductive silver glue in high temperature environments is not ideal, resulting in a decrease in the service life of the device and a high resistivity, which affects the conductive effect.

Method used

Add hydroxyethylated bisphenol fluorene epoxy resin to the matrix resin of conductive silver glue to optimize its composition and form a conjugated structure to reduce resistivity and increase thrust. Combining other epoxy resins and silver powder and other components, through specific Conductive silver glue is prepared by mixing and stirring.

Benefits of technology

It significantly improves the thrust force of conductive silver glue at room temperature and high temperature, reduces resistivity, enhances the conductive effect, and extends the service life of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115595089B_ABST
    Figure CN115595089B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of electronic materials, and provides a conductive silver paste and a preparation method and application thereof. The conductive silver paste comprises a matrix resin and silver powder, and the matrix resin comprises a resin I having a structure as shown in Formula I: #imgabs0# wherein n is an integer of 0 to 5. The conductive silver paste provided by the present invention can significantly improve the room temperature thrust and high temperature thrust of the conductive silver paste by adding the above resin to the matrix resin, and can also reduce the resistivity of the conductive silver paste, improve the conductive effect, and solve the technical problems in the prior art that the conductive effect of the conductive silver paste and the bonding strength under high temperature environment are not ideal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electronic materials, and more specifically, to a conductive silver paste and a preparation method and application thereof. Background Art

[0002] Conductive silver glue is generally composed of base resin and conductive filler. The conductive filler is combined together by the bonding effect of the base resin to form a conductive path, thus realizing conductive bonding between objects. Conductive silver glue can not only avoid material deformation, thermal damage to electronic devices and the formation of internal stress caused by high welding temperature, but also avoid environmental pollution caused by heavy metal lead in tin-lead solder. It can be widely used in the packaging and bonding of electronic components and assemblies such as liquid crystal display screens, light-emitting diodes, integrated circuit chips, printed circuit board components, dot matrix blocks, ceramic capacitors, membrane switches, smart cards, and radio frequency identification.

[0003] The smaller the resistivity of the conductive silver paste, the better its conductive effect. Therefore, how to further reduce the resistivity of the conductive silver paste has always been one of the main improvement directions in the preparation of conductive silver paste.

[0004] In addition, the existing conductive silver paste still has some shortcomings in practical applications. For example, after the conductive silver paste is toughened with toughening resin, the bonding strength at room temperature will be improved, but the bonding strength in a high temperature environment is not ideal, resulting in insufficient adhesion when the device is used in a high temperature environment, ultimately resulting in a significant decrease in the service life of the device. Summary of the invention

[0005] The purpose of the present invention is to address the technical problems in the prior art that the conductive effect of conductive silver paste and the bonding strength under high temperature environment are not ideal, and to provide a conductive silver paste and a preparation method and application thereof. By optimizing the matrix resin composition, the conductive performance of the conductive silver paste is improved, and the thrust of the conductive silver paste at room temperature and high temperature is improved, thereby improving the performance stability and service life of devices using the conductive silver paste.

[0006] The technical solution adopted by the present invention is:

[0007] In a first aspect, the present invention provides a conductive silver paste, comprising a base resin and silver powder, wherein the base resin comprises a resin I having a structure as shown in Formula I:

[0008]

[0009] Here, n is an integer from 0 to 5.

[0010] The inventors of the present application have found in their research that adding hydroxyethylated bisphenol fluorene epoxy resin (resin I) to the base resin of the conductive silver paste can reduce the resistivity of the conductive silver paste and significantly improve the thrust of the conductive silver paste. Specific experiments show that the conductive silver paste with the addition of resin I can improve the room temperature thrust, high temperature thrust and conductive effect compared with the conductive silver paste without the addition of resin I. The beneficial contribution of resin I to the conductive effect of the conductive silver paste may be due to the biphenyl structure contained in the hydroxyethylated bisphenol fluorene epoxy resin, which can form a conjugated structure, which is beneficial to electron transfer and thus is beneficial to reducing the resistivity of the conductive silver paste.

[0011] According to some embodiments of the present invention, taking the total mass of the conductive silver paste as 100%, the mass percentages of the components are:

[0012] Base resin 2-50%;

[0013] Silver powder 50~98%.

[0014] According to some embodiments of the present invention, the base resin further includes other epoxy resins.

[0015] According to some embodiments of the present invention, the mass ratio of the resin I to the other epoxy resin is 1:(0.5-8). For example, the mass ratio of the resin I to the other epoxy resin can be 1:0.5, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, etc.

[0016] According to some embodiments of the present invention, the mass ratio of the resin I to other epoxy resins is 1:(1-3).

[0017] According to some embodiments of the present invention, the other epoxy resin is selected from at least one of glycidyl ether epoxy resin, glycidyl ester epoxy resin and alicyclic epoxy resin.

[0018] According to some embodiments of the present invention, the glycidyl ether epoxy resin is selected from at least one of bisphenol A epoxy resin, allyl bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, hydrogenated bisphenol A epoxy resin, linear phenolic epoxy resin, tetrabromobisphenol A epoxy resin, 4,4-dihydroxydiphenyl sulfone bisglycidyl ether tetraphenol ethane tetraglycidyl ether, resorcinol bisglycidyl ether, 1,3,5-tri(2,3-epoxypropoxy)benzene, resorcinol acetal tetraglycidyl ether, P-(2,3-epoxypropoxy)-N,N-di(2,3-epoxypropyl)aniline, and 1,2-epoxycyclohexane-4,5-dicarboxylic acid epoxy resin.

[0019] According to some embodiments of the present invention, the bisphenol A epoxy resin may be selected from at least one of DER-330, DER-331, DER-332, DER-144, and DER-671 produced by Dow Chemical.

[0020] According to some embodiments of the present invention, the bisphenol F type epoxy resin can be selected from at least one of DER-352, DER-353, DER-354 produced by Dow Chemical Company and DIC830 produced by Dainippon Ink and Chemicals Co., Ltd.

[0021] According to some embodiments of the present invention, the glycidyl ester epoxy resin is selected from at least one of 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexylcarboxylate, 3,4-epoxycyclohexylcarboxylate, tetrahydrophthalate epoxy resin, and diglycidyl phthalate;

[0022] According to some embodiments of the present invention, the alicyclic epoxy resin is selected from at least one of bis(2,3-epoxycyclopentyl) ether and vinylcyclohexene diepoxide.

[0023] According to some embodiments of the present invention, the average particle size of the silver powder is 0.1-20 μm, for example, 0.1 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 5 μm, 9 μm, 13 μm, 15 μm, 18 μm, 20 μm, etc.; preferably 2-13 μm.

[0024] According to some embodiments of the present invention, the specific surface area of ​​the silver powder is 0.01-15m 2 / g, for example, 0.01m 2 / g, 0.1m 2 / g, 0.5m 2 / g, 1m 2 / g, 3m 2 / g, 6m 2 / g, 8m 2 / g, 10m 2 / g, 13m 2 / g, 15m 2 / g, etc.; preferably 0.1-6m 2 / g.

[0025] According to some embodiments of the present invention, the conductive silver paste further includes at least one of a curing agent, a toughening agent, a diluent, a coupling agent, a accelerator, and a reinforcing agent.

[0026] According to some embodiments of the present invention, the curing agent is selected from at least one of anhydride curing agents, amine curing agents, linear synthetic resin oligomer curing agents, and imidazole curing agents.

[0027] According to some embodiments of the present invention, the anhydride curing agent is selected from at least one of phthalic anhydride, tetrahydrophthalic anhydride, trimellitic anhydride glyceride, polyazelaic anhydride, polysebacic anhydride, tung oil anhydride, chlorendic anhydride, tetrabromophthalic anhydride, tetrachlorophthalic anhydride, diphenyl ether tetracarboxylic anhydride, cyclopentanetetracarboxylic anhydride, methyl nadic anhydride, hexahydrophthalic anhydride and methylhexahydrophthalic anhydride.

[0028] According to some embodiments of the present invention, the amine curing agent is selected from m-phenylenediamine, diaminodiphenylmethane, diaminodiphenyl sulfone, polyether diamine, polyarylether diamine, At least one of alkanediamine, N-aminoethylpiperazine, isophordionediamine, 1,3-bis(aminomethyl)cyclohexane, dicarboxyphthalimide, maleimide, hydantoindiamine, aminocyclotrimer phosphazene, and phthalazinone, preferably isophordionediamine or dicarboxyphthalimide.

[0029] According to some embodiments of the present invention, the linear synthetic resin oligomer curing agent is selected from at least one of linear phenolic resin, phenol aralkyl resin, boron phenolic resin, bisphenol A linear phenolic resin, polyvinylphenol resin, aniline formaldehyde resin, N-alkylaniline formaldehyde resin, metaphenylenediamine formaldehyde resin, dicyclopentadiene phenolic resin, and modified phenolic resin, and is preferably a linear phenolic resin.

[0030] According to some embodiments of the present invention, the imidazole curing agent is selected from at least one of dimethylimidazole, 2-ethyl-4-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 2-phenylimidazole, 1-benzyl-2-methylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1,3-dibenzyl-2-methylimidazole chloride, and 2,4-diamino-6-(2-undecylimidazole-1-ethyl)-S-triazine, preferably 2,4-diamino-6-(2-undecylimidazole-1-ethyl)-S-triazine or 1-cyanoethyl-2-ethyl-4-methylimidazole.

[0031] According to some embodiments of the present invention, the toughening agent is selected from at least one of terminal carboxyl liquid nitrile rubber, polyester polyol, polyether polyol, polyamide resin 650, polypropylene oxide rubber, polybutadiene, terminal isocyanate polyether, polysiloxane, dibutyl phthalate, dioctyl phthalate, and polypropylene glycol diglycidyl ether.

[0032] According to some embodiments of the present invention, the diluent is selected from at least one reactive diluent containing epoxy groups and having a viscosity lower than 50 cP.

[0033] According to some embodiments of the present invention, the active diluent includes at least one of dodecyl glycidyl ether, p-tert-butylphenol glycidyl ether, cresol glycidyl ether, ethylene glycol diglycidyl ether, octyl glycidyl ether, butanediol diglycidyl ether, phenyl glycidyl ether, butyl glycidyl ether, polypropylene glycol diglycidyl ether, C12-14 fatty glycidyl ether, benzyl glycidyl ether, and neopentyl glycol diglycidyl ether.

[0034] According to some embodiments of the present invention, the coupling agent is selected from at least one of γ-mercaptopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, vinyltri(β-methoxyethoxy)silane, vinyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, and aminopropyltriethoxysilane.

[0035] According to some embodiments of the present invention, the accelerator is selected from at least one of fatty amine accelerators, substituted urea accelerators, imidazole accelerators, acetylacetone metal salt accelerators, triphenylphosphine and its thiocarboxylic acid metal salts and their complexes, phenol accelerators, quaternary ammonium salt accelerators, thiourea accelerators, peroxide accelerators, and boron trifluoride complexes.

[0036] According to some embodiments of the present invention, the fatty amine accelerator includes at least one of diethylenetriamine, triethylenetetramine, and polyethylenepolyamine.

[0037] According to some embodiments of the present invention, the substituted urea accelerator includes at least one of chlorourea and dimethylimidazole urea.

[0038] According to some embodiments of the present invention, the imidazole accelerator includes at least one of 2-ethyl-4-methylimidazole and 2-methylimidazole.

[0039] According to some embodiments of the present invention, the acetylacetonate metal salt promoter includes at least one of zinc acetylacetonate, copper acetylacetonate, and aluminum acetylacetonate.

[0040] According to some embodiments of the present invention, the triphenylphosphine and its salt promoters include at least one of triphenylphosphine, tetrabutylphosphine chloride (TBPC), tetrabutylphosphine acetate (TBPA), and methyltriphenylphosphine dimethyl phosphate (MTPP-DMP).

[0041] According to some embodiments of the present invention, the carboxylic acid metal salt and its complex include at least one of zinc naphthenate, cobalt naphthenate, manganese naphthenate, calcium naphthenate, and zinc octoate.

[0042] According to some embodiments of the present invention, the phenolic accelerator includes at least one of phenol, o-cresol, m-cresol, and resorcinol.

[0043] According to some embodiments of the present invention, the quaternary ammonium salt accelerator is benzyltriethylammonium chloride.

[0044] According to some embodiments of the present invention, the thiourea accelerator includes at least one of allylthiourea, ethylenethiourea, and organic guanidines such as tetramethylguanidine.

[0045] According to some embodiments of the present invention, the peroxide accelerator includes at least one of benzoyl peroxide and tert-butyl perbenzoate.

[0046] According to some embodiments of the present invention, the boron trifluoride complex promoter includes at least one of boron trifluoride monoethylamine, boron trifluoride methyl ether, boron trifluoride imidazole, boron trifluoride methyl imidazole, boron trifluoride piperidine, and boron trifluoride phenol.

[0047] According to some embodiments of the present invention, the reinforcing agent is selected from at least one of nano-silicon dioxide, nano-calcium carbonate, nano-titanium dioxide, nano-zinc oxide, nano-aluminum oxide or nano-aluminum nitride; preferably nano-silicon dioxide.

[0048] According to some embodiments of the present invention, the particle size of the nano-silica is 1-500 nm, for example, 1 nm, 5 nm, 10 nm, 50 nm, 100 nm, 150 nm, 200 nm, 300 nm, 400 nm, 500 nm, etc.

[0049] In the present invention, the reinforcing agent is preferably nano-silicon dioxide, mainly to increase thixotropy and prevent the silver powder from settling during storage and use of the silver colloid.

[0050] According to some embodiments of the present invention, taking the total mass of the conductive silver paste as 100%, the mass percentages of the components are:

[0051]

[0052] In a second aspect, the present invention provides a method for preparing the conductive silver paste described in the first aspect, characterized in that it comprises: mixing the components to obtain the conductive silver paste.

[0053] According to some embodiments of the present invention, the mixing uses a planetary stirring mixing device, the rotation rate is 30-90% of the revolution rate, the revolution rate is 400-2500 revolutions per minute, and the stirring time is 2-20 minutes; preferably, the rotation rate is 60-80% of the revolution rate, the revolution rate is 1500-2500 revolutions per minute, and the stirring time is 10-20 minutes. For example, the rotation rate of the planetary stirring mixing device is 70% of the revolution rate, the revolution rate is 2200 revolutions per minute, and the stirring time is 15 minutes.

[0054] According to some embodiments of the present invention, the method for preparing the resin I comprises: obtaining the resin by reacting ethoxylated bisphenol fluorene with a chloroalkyl compound under alkaline conditions.

[0055] The ethoxylated bisphenol fluorene has a general structure as shown in Formula II:

[0056]

[0057] According to some embodiments of the present invention, the chloroalkyl compound is epichlorohydrin.

[0058] According to some embodiments of the present invention, the preparation method of the resin I specifically includes: adding sodium hydroxide to a mixed solution of ethoxylated bisphenol fluorene glycol, a chloroalkyl compound and a solvent at 50-80°C; after the reaction is completed, adding toluene to wash until neutral, separating the organic phase, and performing reduced pressure distillation to obtain the resin I.

[0059] According to some embodiments of the invention, the solvent is dimethyl sulfoxide.

[0060] According to some embodiments of the present invention, the adding of sodium hydroxide is performed in batches.

[0061] According to some embodiments of the present invention, the reaction time is 4-10 hours.

[0062] According to some embodiments of the present invention, the molar ratio of the ethoxylated bisphenol fluorene glycol to the chloroalkyl compound is 1:(5-20), for example 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19, 1:20, etc.

[0063] According to some embodiments of the present invention, the molar ratio of the ethoxylated bisphenol fluorene glycol to sodium hydroxide is 1:(7-12), for example 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, etc.

[0064] According to some embodiments of the present invention, the molar ratio of the ethoxylated bisphenol fluorene glycol to the solvent is 1:(0.1-2.6), for example, 1:0.1, 1:0.5, 1:1, 1:1.5, 1:1.8, 1:2, 1:2.3, 1:2.6, etc.

[0065] In a third aspect, the present invention provides an application of the conductive silver paste described in the first aspect or the conductive silver paste prepared by the preparation method described in the second aspect in the packaging and bonding of electronic components and assemblies of liquid crystal displays, light-emitting diodes, integrated circuit chips, printed circuit board assemblies, dot matrix blocks, ceramic capacitors, membrane switches, smart cards, and radio frequency identification.

[0066] The beneficial effects of the present invention are at least:

[0067] The conductive silver paste provided by the present invention can significantly improve the room temperature thrust and high temperature thrust of the conductive silver paste by adding hydroxyethylated bisphenol fluorene epoxy resin, and can also reduce the resistivity of the conductive silver paste, thereby improving the conductive effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0068] Figure 1 It is a schematic diagram of the thrust testing method in the present invention. DETAILED DESCRIPTION

[0069] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain this patent in detail and do not limit the scope of protection of the present invention in any way.

[0070] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the reagent amounts, unless otherwise specified, are the reagent amounts used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.

[0071] In each embodiment and comparative example of the present invention, the materials used are as follows:

[0072] Ethoxylated bisphenol fluorene glycol (BHEPF-2 / BHEPF-4 / BHEPF-6): Liaoning Hongtai Pharmaceutical Co., Ltd., purity 98%;

[0073] Bisphenol F type epoxy resin: DIC830, Dainippon Ink;

[0074] Linear phenolic resin: 8101, Shengquan Group;

[0075] Other raw materials are commercially available.

[0076] The relevant performance testing methods in the embodiments and comparative examples of the present invention are as follows:

[0077] (1) Thrust test:

[0078] The thrust machine test was conducted. The manufacturer of the thrust machine was Dage Precision Industries Ltd and the model was DAGE-SERIES-4000PXY.

[0079] The specific test method of thrust test is as follows: the chip size is 8mil*8mil, the chip and the silver plate are bonded with conductive silver glue, and the chip is pushed with a thrust machine until it is pushed off, and the data is recorded.

[0080] 2) Resistivity test

[0081] A resistivity tester was used, the equipment being a digital micro-ohmmeter model ZY9987 produced by Shanghai Zhengyang Instrument; the sample was a cubic strip, 66 mm long, 4 mm wide and 0.1 mm thick.

[0082] Preparation Example 1

[0083] Preparation of DGEBEF-2 (n=1):

[0084] BHEPF-2 (43.8 g, 0.1 mol), epichlorohydrin (92.5 g, 1 mol) and dimethyl sulfoxide (13.7 g, 0.18 mol) were added to a 500 mL three-necked flask equipped with a mechanical stirrer, a thermometer, a water condenser and a nitrogen inlet. The flask was heated to 55° C. to completely dissolve BHEPF-2. 6 g of sodium hydroxide was added every 0.5 h for a total of 4 times. After reacting for 1 h, 12 g of sodium hydroxide was added again. The reaction was then terminated after 2.5 h. After the reaction was completed, 200 mL of toluene was added, and the mixture was washed with deionized water several times to a neutral pH value. The organic phase was separated; toluene, dimethyl sulfoxide and excess epichlorohydrin were distilled out under reduced pressure to obtain a light yellow liquid DGEBEF-2 with a yield of 92%.

[0085]

[0086] The yield of this preparation example was calculated according to the following formula:

[0087] Yield = actual mass of DGEBEF-2 finally obtained / (molar amount of BHEPF-2*molecular mass of DGEBEF-2)*100%.

[0088] Preparation Example 2

[0089] Preparation of DGEBEF-4 (n=2):

[0090] The preparation method refers to Preparation Example 1, except that BHEPF-2 (43.8 g, 0.1 mol) is replaced with BHEPF-4 (52.6 g, 0.1 mol) to obtain light yellow liquid DGEBEF-4 with a yield of 91%.

[0091]

[0092] Preparation Example 3

[0093] Preparation of DGEBEF-6 (n=3):

[0094] The preparation method refers to Preparation Example 1, except that BHEPF-2 (43.8 g, 0.1 mol) is replaced with BHEPF-6 (61.4 g, 0.1 mol) to obtain light yellow liquid DGEBEF-6 with a yield of 90%.

[0095]

[0096] Example 1

[0097] Preparation of conductive silver paste: weigh 6g bisphenol F epoxy resin, 4g isophordine diamine, 3g DGEBEF-2 resin, 76g silver powder (average particle size 3μm, specific surface area 0.5m 2 / g), 8g of butanediol diglycidyl ether, 0.5g of dibutyl phthalate, 1g of γ-glycidyloxypropyltrimethoxysilane, 0.5g of triphenylphosphine and 1g of nano-silicon dioxide (average particle size 100nm) are added into a stirring cup, and a planetary stirring mixing equipment is used. The revolution speed is 2200 rpm, and the rotation speed rate is 70% of the revolution speed. Stir for 15 minutes to obtain the mixed silver glue 1#.

[0098] Example 2

[0099] The preparation method of the conductive silver paste refers to Example 1, and the only difference from Example 1 is that 3 g of DGEBEF-2 resin is replaced by 3 g of DGEBEF-4 resin to obtain silver paste 2#.

[0100] Example 3

[0101] The preparation method of the conductive silver paste refers to Example 1, and the only difference from Example 1 is that 3 g of DGEBEF-2 resin is replaced by 3 g of DGEBEF-6 resin to obtain silver paste 3#.

[0102] Example 4

[0103] The preparation method of the conductive silver paste refers to Example 1, and the only difference from Example 1 is that 3 g of DGEBEF-2 resin is replaced by 6 g of DGEBEF-6 resin to obtain silver paste 4#.

[0104] Example 5

[0105] The preparation method of the conductive silver paste refers to Example 1, and the only difference from Example 1 is that 6g of bisphenol F epoxy resin is replaced by 6g of P-(2,3-epoxypropoxy)-N,N-di(2,3-epoxypropyl)aniline to obtain silver paste 5#.

[0106] Example 6

[0107] The preparation method of the conductive silver paste refers to Example 1, and the only difference from Example 1 is that 1g of γ-glycidyloxypropyltrimethoxysilane is replaced with 1g of γ-aminopropyltriethoxysilane to obtain silver paste 6#.

[0108] Example 7

[0109] The preparation method of the conductive silver paste refers to Example 1, and the only difference from Example 1 is that 4 g of isophordione diamine is replaced by 4 g of linear phenolic resin to obtain silver paste 7#.

[0110] Example 8

[0111] The preparation method of the conductive silver paste refers to Example 1, and the only difference from Example 1 is that 6g of bisphenol F epoxy resin and 3g of DGEBEF-2 resin are replaced with 9g of DGEBEF-2 resin to obtain silver paste 8#.

[0112] Example 9

[0113] Preparation of conductive silver paste: weigh 30g bisphenol F epoxy resin, 4g isophordine diamine, 3g DGEBEF-2 resin, 52g silver powder (average particle size 3μm, specific surface area 0.5m 2 / g), 8g of butanediol diglycidyl ether, 0.5g of dibutyl phthalate, 1g of γ-glycidyloxypropyltrimethoxysilane, 0.5g of triphenylphosphine and 1g of nano-silicon dioxide (average particle size 100nm) are added into a stirring cup, and a planetary stirring mixing equipment is used. The revolution speed is 2200 rpm, and the rotation speed rate is 70% of the revolution speed. Stir for 15 minutes to obtain the mixed silver glue 9#.

[0114] Comparative Example 1

[0115] The preparation method of the conductive silver paste refers to Example 1, and the only difference from Example 1 is that 6g of bisphenol F epoxy resin and 3g of DGEBEF-2 resin are replaced by 9g of bisphenol F epoxy resin to obtain silver paste 10#.

[0116] Comparative Example 2

[0117] The preparation method of the conductive silver paste refers to Example 1, and the only difference from Example 1 is that 3 g of DGEBEF-2 resin is replaced by 3 g of DGEBAEO-2 resin to obtain silver paste 11#.

[0118]

[0119] After testing, the room temperature thrust, high temperature (160° C.) thrust, and resistivity test results of the conductive silver paste of the above embodiments and comparative examples are shown in Table 1 below:

[0120] Table 1

[0121] Room temperature thrust / g 160℃ thrust / g Resistivity Ω·cm Silver glue 1# 196 137 2.82E-04 Silver glue 2# 224 128 2.80E-04 Silver glue 3# 238 119 2.79E-04 Silver glue 4# 242 121 2.47E-04 Silver glue 5# 185 145 2.83E-04 Silver glue 6# 202 141 2.84E-04 Silver glue 7# 216 147 2.80E-04 Silver glue 8# 204 137 2.12E-04 Silver glue 9# 166 107 1.41E-02 Silver glue 10# 150 105 3.53E-04 Silver glue 11# 213 118 3.54E-04

[0122] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

Claims

1. A conductive silver paste, comprising a matrix resin and silver powder, characterized in that: The base resin includes a resin I having a structure as shown in Formula I: Here, n is an integer from 1 to 5.

2. The conductive silver paste according to claim 1, characterized in that: Taking the total mass of the conductive silver paste as 100%, the mass percentage of each component is: Base resin 2-50%; Silver powder 50~98%.

3. The conductive silver paste according to claim 1 or 2, characterized in that: The matrix resin also includes other epoxy resins.

4. The conductive silver paste according to claim 3, characterized in that: The mass ratio of the resin I to other epoxy resins is 1:(0.5-8).

5. The conductive silver paste according to claim 4, characterized in that: The mass ratio of the resin I to other epoxy resins is 1:(1-3).

6. The conductive silver paste according to claim 3, characterized in that: The other epoxy resin is selected from at least one of glycidyl ether epoxy resin, glycidyl ester epoxy resin and alicyclic epoxy resin.

7. The conductive silver paste according to claim 6, characterized in that: The glycidyl ether epoxy resin is selected from at least one of bisphenol A epoxy resin, allyl bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, hydrogenated bisphenol A epoxy resin, linear phenolic epoxy resin, tetrabromobisphenol A epoxy resin, 4,4-dihydroxydiphenyl sulfone bisglycidyl ether tetraphenol ethane tetraglycidyl ether, resorcinol bisglycidyl ether, 1,3,5-tris(2,3-epoxypropoxy)benzene, p-resorcinol acetal tetraglycidyl ether, P-(2,3-epoxypropoxy)-N,N-di(2,3-epoxypropyl)aniline, and 1,2-epoxycyclohexane-4,5-dicarboxylic acid epoxy resin; And / or, the glycidyl ester epoxy resin is selected from at least one of 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexylcarboxylate, 3,4-epoxycyclohexylcarboxylate, tetrahydrophthalate epoxy resin, and diglycidyl phthalate; And / or, the alicyclic epoxy resin is selected from at least one of bis(2,3-epoxycyclopentyl) ether and vinylcyclohexene diepoxide.

8. The conductive silver paste according to claim 1 or 2, characterized in that: The average particle size of the silver powder is 0.1-20 μm; and / or the specific surface area of ​​the silver powder is 0.01-15 m 2 / g.

9. The conductive silver paste according to claim 8, characterized in that: The average particle size of the silver powder is 2-13 μm; and / or the specific surface area of ​​the silver powder is 0.1-6 m 2 / g.

10. The conductive silver paste according to claim 1 or 2, characterized in that: The conductive silver paste further comprises at least one of a curing agent, a toughening agent, a diluent, a coupling agent, a accelerator, and a reinforcing agent.

11. The conductive silver paste according to claim 10, characterized in that: The curing agent is selected from at least one of anhydride curing agents, amine curing agents, linear synthetic resin oligomer curing agents, and imidazole curing agents; And / or, the toughening agent is selected from at least one of carboxyl-terminated liquid nitrile rubber, polyester polyol, polyether polyol, polyamide resin 650, polypropylene oxide rubber, polybutadiene, isocyanate-terminated polyether, polysiloxane, dibutyl phthalate, dioctyl phthalate, and polypropylene glycol diglycidyl ether; And / or, the diluent is selected from at least one reactive diluent containing epoxy groups and having a viscosity lower than 50 cP; And / or, the coupling agent is selected from at least one of γ-mercaptopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, vinyltri(β-methoxyethoxy)silane, vinyltrimethoxysilane, γ-mercaptopropyltriethoxysilane and aminopropyltriethoxysilane; And / or, the accelerator is selected from at least one of aliphatic amine accelerators, substituted urea accelerators, imidazole accelerators, acetylacetone metal salt accelerators, triphenylphosphine salt accelerators, carboxylic acid metal salts and complexes thereof, phenol accelerators, quaternary ammonium salt accelerators, thiourea accelerators, peroxide accelerators, and boron trifluoride complexes; And / or, the reinforcing agent is selected from at least one of nano silicon dioxide, nano calcium carbonate, nano titanium dioxide, nano zinc oxide, nano aluminum oxide or nano aluminum nitride.

12. The conductive silver paste according to claim 11, characterized in that: The reinforcing agent is selected from nano silicon dioxide.

13. The conductive silver paste according to claim 12, characterized in that: The reinforcing agent is selected from nano silicon dioxide with an average particle size of 1-500nm.

14. The conductive silver paste according to claim 10, characterized in that: Taking the total mass of the conductive silver paste as 100%, the mass percentage of each component is: Base resin 2-30%; Silver powder 50-90%; Curing agent 2-30%; Toughening agent 0.1~30%; Diluent 1~30%; Coupling agent 0.01~3%; Accelerator 0.01~5%; Enhancer 0.1~10%.

15. The method for preparing the conductive silver paste according to any one of claims 1 to 14, characterized in that: include: The conductive silver paste can be prepared by mixing the components.

16. The preparation method according to claim 15, characterized in that: The mixing uses a planetary stirring mixing device, the rotation rate is 30-90% of the revolution rate, the revolution rate is 400-2500 revolutions per minute, and the stirring time is 2-20 minutes.

17. An application of the conductive silver paste according to any one of claims 1 to 14 or the conductive silver paste prepared by the preparation method according to claim 15 or 16 in the packaging and bonding of electronic components and assemblies of liquid crystal display screens, light emitting diodes, integrated circuit chips, printed circuit board components, dot matrix blocks, ceramic capacitors, membrane switches, smart cards, and radio frequency identification.